CONCEPT EXTENT OF SEVERITY ICHTHYOSIS - Дмитренко, С.В. (World of Medicine and Biology, 2015)
Aim of our work – proposed criteria for the use of different variants of flow that determines the optimal tactics of treatment.Ichthyosis is the most common henodermatozom in the world and Ukraine, which includes a heterogeneous group of species with different disease etiology, intensity of symptoms and prevalence of lesions. Ichthyosis is defined as a heterogeneous group of diseases with several subspecies, and there are views of ichthyosis, who see it as a heterogeneous disease that has individual manifestations of genetic disorders. Current proposals for classification ichthyosis into account its heterogeneity. However, these recommendations do not indicate the need for finding different severity of the disease, which is why, diagnosis and management of ichthyosis is quite complicated problem. The course of ichthyosis is little known and urgent task in dermatology. New data on the etiology and pathogenesis of the disease, current therapies require a comprehensive approach to evaluation.Materials and methods We conducted a cohort study and analysis of clinical and laboratory features of 70 patients with ichthyosis ichthyosis respect to age, gender, living and working conditions, the presence of harmful habits, heredity, number of calls per year, the date of diagnosis, concomitant diseases. All patients diagnosed according to clinical guidelines MH of Ukraine and made the recommended minimum level of clinical and laboratory research. All patients were in clinical supervision. dermatologist at the residence during the period 2010 - 2014 years, treated according to the protocols of medical care MoH Ukraine. A survey of patients conducted at the residence and when accessing the Regional STI clinic. In addition to research methods Standart patients conducted DNA cytometry, immunological, immunohistochemical, dermatoskopichni, dermatoglyphic, the study of quality of life according to standardized methods.The sample of patients randomly conducted, results analyzed statistical methods recommended for cohort studies in the software package "STATISTICA 5.5" (CNIT VNMU belongs to them. Pirogov, license № AXXR910A374605FA.Results. DiscussionsWe conducted a comprehensive obste6zhennya 70 patients with ichthyosis suggest heterogeneity of clinical and laboratory signs of progress ichthyosis. Identified changes correlated relatively manifestations and severity of strengthening the presence of signs of damage to the body at different levels from the molecular to the general indicators of clinical and QOL. The main result of our study was to determine the main clinical and laboratory features that distinguish allow easy and difficult disease.The main clinical manifestations are characterized by severe burdened heredity, increased hospitalizations polimorfnistyu skin and complaints need retinoid application to control the disease. The overall incidence of hospitalizations in patients with ichthyosis was quite low - less than once a year, identified a group of patients - 8 of 70 in the condition required hospitalization 2-3 times or more a year. The most common manifestation in patients was dry and skin tightening - 100 and 96% respectively, slightly less - 80% of patients experienced itching least represented symptom was pain that bothered 10% of patients.In most patients, the combination of skin lesions observed upper or lower limbs and trunk (68%) of the 8 people that already belonged to the group of severe which was a combination of 4 or more locations destruction. Among dermatoglyphics features only essential feature is the identification chotyrohpaltsevoyi flexural creases with ichthyosis. According to our records, it was detected in 11 of 47 patients with ichthyosis (22%). These patients were 7 men and 4 women. Also in this group included 6 patients who had severe course ichthyosis and marked clinical signs.Note that among 8 patients with severe ichthyosis use retinol palmitate proved effective only in 2 patients, only 6 other combination therapy with topical retinoids (radevit, videstym, redetsyl) resulted in clinically significant results. Serious side effects at the local and systemic use retinoids us not observed.Against the backdrop of severe ichthyosis proved significantly higher rates of proliferation index, interval SUB-G0G1, S phase and significantly reduced performance phase G2 + M. Patients with ichthyosis are complete violation of immunity, more pronounced in cell link - immunological differences in a significant increase of IgA, reduce immunoregulatory index CD4 / CD8 in the group with severe relative to the control group and the group of indicators mild (p
Keywords: ichthyosis; severity; symptoms; treatment; diagnostic criteria